Stable Magnetic Universes Revisited - Tahamtan, Tayebeh; Halilsoy, Mustafa (Astrophysics and Space Science, Springer, 2013)
A regular class of static, cylindrically symmetric pure magnetic field metrics is rederived in a different metric ansatz in all dimensions. Radial, time dependent perturbations show that for dimensions d>3 such spacetimes are stable at both near r\approx0 and large radius r\rightarrow\infty. In a different gauge these stability analysis and similar results were known beforehand. For d=3, however, simultaneous stability requirement at both, near and far radial distances can not be reconciled for time - dependent perturbations. Restricted, numerical geodesics for neutral particles reveal a confinement around the center in the polar plane. Charged, time-like geodesics for d=4 on the other hand are shown numerically to run toward infinity.
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1007/s10509-012-1217-0) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: general relativity; universe; Magnetic universe; Perturbation; Gravitational confinement